2004
DOI: 10.1111/j.1365-2303.2004.00194.x
|View full text |Cite
|
Sign up to set email alerts
|

Five‐year follow‐up of women with borderline and mildly dyskaryotic cervical smears

Abstract: This study investigated the 5-year follow-up status of women with cervical smears showing borderline nuclear changes (BNC) or mild dyskaryosis and the effect of koilocytosis on the outcome. Thirteen per cent of women with cervical smears showing BNC had high-grade cervical intraepithelial neoplasia (CIN). In contrast, 28% of women with cervical smears showing mild dyskaryosis had high-grade CIN. The presence of koilocytosis (24% for borderline smears and 34% for mild dyskaryotic smears) did not appear to influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 25 publications
4
25
1
Order By: Relevance
“…Firstly, the ratio of BNA to mild cytology results among trial recruits was similar to that observed in the CSPs [16]. Secondly, the cumulative incidence of CIN2/3 during follow-up was similar to that observed in other studies conducted within the screening programme [52], [53]. Moreover, TOMBOLA was a pragmatic trial and the management policies evaluated mimicked those offered by the CSPs.…”
Section: Discussionsupporting
confidence: 77%
“…Firstly, the ratio of BNA to mild cytology results among trial recruits was similar to that observed in the CSPs [16]. Secondly, the cumulative incidence of CIN2/3 during follow-up was similar to that observed in other studies conducted within the screening programme [52], [53]. Moreover, TOMBOLA was a pragmatic trial and the management policies evaluated mimicked those offered by the CSPs.…”
Section: Discussionsupporting
confidence: 77%
“…The extent of the underestimation is probably small, however, as only 32 new cases were found at the exit examination (2.4% of attendees). In addition, the incidence of cervical intraepithelial neoplasia grade II or worse up to, but not including, the exit examination (14% and 33% for those with recruitment smears showing borderline nuclear abnormalities and mild dyskaryosis, respectively), were similar to figures from two studies that followed participants in the NHS cervical screening programme with borderline nuclear abnormalities and mild dyskaryosis for five years (13% and 28%, 44 13% and 36% 45 ). When we restricted our analysis to women who had attended the exit examination, the results were unchanged (adjusted relative risk for grade II or worse, large loop excision v biopsy 1.02, 0.81 to 1.28).…”
Section: Strengths and Limitationssupporting
confidence: 68%
“…Although, the majority of such abnormalities will clear in time, a proportion will develop or harbour high-grade lesions that warrant investigation (Kinney et al, 1998;Rana et al, 2004).…”
Section: Introductionmentioning
confidence: 99%